KALIMAT TANYA DALAM BAHASA MANDAILING: TEORI X-BAR - Soraya Tsamara Zahra; Mulyadi Mulyadi (Universitas Negeri Makassar, 2019)
Interrogative Sentence in Mandailing Language: X-bar Theory. This study aims to analyze grammatical and lexical structure in interrogative sentence in Mandailing language. The study of this interrogative sentence structure applies X-bar theory as one of the generative syntax subtheories. This type of research includes qualitative research using distributional method. The data were collected through interview and observation. The result of the study showed that the wh-question in Mandailing language had grammatical function as spesifier and komplement, while the total question sentence had a function as a komplement. Interrogative sentence in Mandailing language formed by spesifiers, komplements, and adverb.